Strategi Pemanfaatan Facebook Marketplace dalam Manajemen Periklanan - Arizal Arizal; Rika Apriany Sukmana; Yusrina Ulfah; Syahrial Shaddiq; Mohammad Zainul (Ridwan Institute, 2021)
In this digital era, social media has grown into a scourge of millennial life. Social media adorns almost all platforms, both the business world, the world of information, to other lifestyles, it is like the necessities of life for the millennial community. One of the social media platforms that is busy being used by users is the Facebook marketplace application where in this application we can get both information, websites and social media. buying and selling, and communication. Buying and selling online through a marketplace platform provided by Facebook which is used to design and implement the conception, distribution of goods, ideas, and services that will be exchanged to individuals or groups to fulfill needs. So this study aims to clearly see the role of the facebook marketplace platform as a media marketplace that is much needed by the public and a marketing strategy that is usually done in the facebook marketplace social media. The research method used is descriptive literature study. This research discusses about Bintang Jaya Grafika as one of the sellers who use the platform as a promotional material. This is a creative marketing strategy to attract buyers. The use of a Facebook marketplace can be a new idea in a cheap and effective marketing strategy in increasing sales and good promotions.